Role of international organizatıons in regional cooperation : case study of Azerbaijan in the system of organization of Islamic cooperation - Mehdiyev, Elmaddin (My University, 2019)
BÖLGESEL İŞBİRLİĞİNDE ULUSLARARASI ÖRGÜTLERİN ROLÜ: İSLAM İŞBİRLİĞİ TEŞKİLATI SİSTEMİNDE AZERBAYCAN ÖRNEĞİ İslam İşbirliği Teşkilatı (İİT) odaklı uluslararası örgütlerin bölgesel işbirliğindeki rolünü yorumlayan literatürün yakından incelenmesi, bu konuların yüzeysel araştırılmasının yanı sıra ilgili literatürün çok yetersiz olduğunu ortaya koymaktadır. Genel olarak, uluslararası örgütlerin bölgesel işbirliğine belirli katkıları hakkında literatür fazla değildir. Bu boşluklara dayanarak, bu çalışmada İslam İşbirliği Teşkilatı kapsamında Azerbaycan örneğini ele alarak, söz konusu uluslararası örgütün bölgesel işbirliğindeki rolünün araştırılması amaçlanmaktadır. Bu çalışmanın hedefi, İslam İşbirliği Teşkilatı (İİT) gibi uluslararası bir kuruluşun Azerbaycan'ı ekonomik, kültürel ve politik olarak nasıl etkilediğini araştırmaktır. Ayrıca, araştırma Azerbaycan’ın İİT’e üyeliğinin hem bölgesel hem de uluslararası açıdan üye ülkelerle ikili ve çok taraflı ilişkilerini nasıl etkilediğini incelemeye çalışmıştır.

ROLE OF INTERNATIONAL ORGANIZATIONS IN REGIONAL COOPERATION: CASE STUDY OF AZERBAIJAN IN THE SYSTEM OF ORGANIZATION OF ISLAMIC COOPERATION A close look of literature commenting on the role of international organizations in regional cooperation with a view of Organization of Islamic Cooperation (OIC) reveals very scant as well as superficial examination of such issues. In general, literature on the specific contributions of international organizations in regional cooperation are few. Based on such gaps, this study aims to investigate the role of specific international organization in regional cooperation by examining a case study of Azerbaijan within the realms of the Organization of Islamic Cooperation. The purpose of this study is to research how an international organization like the OIC influences Azerbaijan economically, culturally, and politically. In addition, the study sought to examine how Azerbaijan’s membership to the OIC affects its bilateral and multilateral relations with member countries, both, from the regional and international point of view.
Keywords: Azerbaycan; Bölgesel İşbirliği; International Organizations; International relations; İslam İşbirliği Teşkilatı; Organization of Islamic Cooperation; Political science; Regional Cooperation; Siyasal bilim; Uluslararası ilişkiler; Uluslararası Organizasyonlar Azerbaijan